Literature Review on the Association between Earnings Management and Corporate Social Responsibility - Parvin, Ruksana; Sohel Rana, Md.; Shams, Shahpar (International Journal of Accounting & Finance Review, 2020)
This paper aims to give an overview of the existing literature on the Earnings Management (EM) and Corporate Social Responsibility (CSR) relationship in different countries. This paper reviews preceding studies concerned about EM, CSR and their relationship. Out of 23 works of literature, 11 studies found a negative relationship, 6 studies found a positive relationship, 2 studies found blended relationships in case of different situations and 4 studies found no connection between CSR and EM. Most of the results demonstrated that probably the socially responsible organizations have a negative correlation with EM practice. The types of the relationship depend on cause-effect relationship, information asymmetry, how can a company use resources, awareness on environmental issues, awareness on ethical issues, tax avoidance tendency, corporate governance practice, nature of the firm, political environment, opportunistic incentive, and stakeholder capital, manager's psychology, etc. Relationships between EM and CSR influence on earnings quality, firm performance, and firm value.